Multilevel Permutation with Different Block Size/ Stream Cipher Image Encryption - Jasim, Abbas A.; Hakim, Hiba (Iraqi Journal for Electrical and Electronic Engineering, 2015)
In this work, a new image encryption method using a combined multilevel permutation with stream cipher is proposed. In the permutation algorithm, image is divided into blocks in each level and its blocks are rearranged by using pseudorandom permutation method. A new non linear stream cipher algorithm is also proposed that is based on combining several keys generated by Linear Feedback Shift Register (LFSR). The results shown that the proposed algorithm has a high security feature and it is efficient for image encryption. Practical tests proved that the proposed encryption algorithm is robust, provides high level of security and gives perfect reconstruction of the decrypted image.